Ten questions concerning occupant behavior in buildings: The big picture. (March 2017) - Hong, Tianzhen; Yan, Da; D'Oca, Simona; Chen, Chien-fei
Abstract: Occupant behavior has significant impacts on building energy performance and occupant comfort. However, occupant behavior is not well understood and is often oversimplified in the building life cycle, due to its stochastic, diverse, complex, and interdisciplinary nature. The use of simplified methods or tools to quantify the impacts of occupant behavior in building performance simulations significantly contributes to performance gaps between simulated models and actual building energy consumption. Therefore, it is crucial to understand occupant behavior in a comprehensive way, integrating qualitative approaches and data- and model-driven quantitative approaches, and employing appropriate tools to guide the design and operation of low-energy residential and commercial buildings that integrate technological and human dimensions. This paper presents ten questions, highlighting some of the most important issues regarding concepts, applications, and methodologies in occupant behavior research. The proposed questions and answers aim to provide insights into occupant behavior for current and future researchers, designers, and policy makers, and most importantly, to inspire innovative research and applications to increase energy efficiency and reduce energy use in buildings. Highlights: A big picture of building energy–related occupant behavior research is offered. Advantages and challenges of integrating behavior in building life cycle are discussed. Advances in behavior sensing, analytics, modeling, and simulation are presented. An interdisciplinary perspective incorporating social science and engineering research is outlined. Future research and information sources are recommended.